Polyacrylic Acid‐Coated Selenium‐Doped Carbon Dots Inhibit Ferroptosis to Alleviate Chemotherapy‐Associated Acute Kidney Injury - Jiahuan Li; Chengcheng Fu; Baoli Feng; Qingquan Liu; Jiangjiang Gu; Mohammad Nauman Khan; Lvhui Sun; Honghong Wu; Hao Wu (Advanced Science, 2024)
Abstract Cisplatin‐associated acute kidney injury (AKI) is a severe clinical syndrome that significantly restricts the chemotherapeutic application of cisplatin in cancer patients. Ferroptosis, a newly characterized programmed cell death driven by the lethal accumulation of lipid peroxidation, is widely reported to be involved in the pathogenesis of cisplatin‐associated AKI. Targeted inhibition of ferroptosis holds great promise for developing novel therapeutics to alleviate AKI. Unfortunately, current ferroptosis inhibitors possess low bioavailability or perform non‐specific accumulation in the body, making them inefficient in alleviating cisplatin‐associated AKI or inadvertently reducing the anti‐tumor efficacy of cisplatin, thus not suitable for clinical application. In this study, a novel selenium nanomaterial, polyacrylic acid‐coated selenium‐doped carbon dots (SeCD), is rationally developed. SeCD exhibits high biocompatibility and specifically accumulates in the kidney. Administration of SeCD effectively scavenges broad‐spectrum reactive oxygen species and significantly facilitates GPX4 expression by releasing selenium, resulting in strong mitigation of ferroptosis in renal tubular epithelial cells and substantial alleviation of cisplatin‐associated AKI, without compromising the chemotherapeutic efficacy of cisplatin. This study highlights a novel and promising therapeutic approach for the clinical prevention of AKI in cancer patients undergoing cisplatin chemotherapy.